Hyper-Visible Yet Invisible: Exploring the Body Image Experiences of Overweight Women in Everyday Life - Panagiota Tragantzopoulou (Obesities, 2025)
Weight stigma remains a pervasive issue in contemporary society, impacting individuals’ psychological well-being, social inclusion, and access to opportunities. This study explored the lived experiences of overweight women, focusing on body image, stigma, and engagement with dominant health and beauty norms. Using a qualitative, phenomenological approach, online in-depth interviews were conducted with 14 women aged 25 to 51, primarily residing in southern and eastern Europe (Greece, Cyprus, Albania, Romania, and Bulgaria), with three participants from the United Kingdom. Thematic analysis revealed four key themes: workplace discrimination, pressures during pregnancy and the postpartum period, ambivalence toward body positivity movements, and the emotional toll of stigma, including extreme coping strategies. Participants described being marginalized professionally, scrutinized publicly and within families, and caught between ideals of inclusivity and persistent societal rejection. The findings emphasize the psychological burden of weight-based discrimination and the superficial nature of many body acceptance campaigns. This study calls for structural changes in healthcare, media, and employment practices to support body diversity and dismantle entrenched biases. By centering the voices of overweight women, the research contributes to broader discussions on embodiment, social justice, and intersectionality within the field of body image scholarship.